An Empirical Study of the Application of Dynamic Assessment in EFL Students’ Academic Writing - Abdalkarim Amin Al Zangana, Aras; Farooq Jawad, Hoshang (The Scientific Journal of Cihan University– Sulaimaniya, 2023)
This study investigates the impact of Dynamic Assessment (henceforth DA) on the academic writing skills of Kurdish EFL university students. In this study 28 second-stage students at Cihan University- Sulaimaniya participated. They were divided into two groups: a control group, which received traditional teaching and assessment method, and an experimental group, which received teaching and assessment based on the DA sandwich format. Over the course of 15 sessions, both groups underwent a pre-test, followed by the experimental group’s exposure to DA and the control group’s adherence to traditional methods. A post-test was administered to both groups to evaluate any significant differences in their academic writing abilities. One-Way ANOVA analysis was conducted to examine these differences. The results revealed a substantial improvement in the academic writing performance of the experimental group exposed to DA compared to the control group. This improvement underscored the efficacy of DA in enhancing students’ writing abilities. Additionally, DA was found to alleviate students’ anxiety and promote active involvement in self-reflection, error identification, and collaborative problem-solving with a mediator. The pedagogical implications of this study highlight the advantages of a student-centered, participatory assessment approach over a teacher-centered one. They underline the need for educators to adapt their teaching methods to foster critical thinking, self-correction skills, and active student engagement, ultimately facilitating students’ performance in the academic writing.